BIOMONITORING KUALITAS UDARA MENGGUNAKAN CAPUNG (Orthetrum sabina) - Fhina Marisya Putri; Nutrinem; Slamet Mardiyanto Rahayu (Nusadaya Journal of Multidiciplinary Studies, 2025)
Air pollution in urban areas triggered by vehicle emissions and industrial activities requires biological monitoring methods capable of demonstrating the cumulative impact of pollutants. Orthetrum sabina is a dragonfly species characterized by high mobility yet territorial behavior, making it highly effective as a bioindicator of air quality within specific areas. The biomonitoring focus on this species lies in its ability to absorb and store heavy metal residues and atmospheric particulates in its wing and thorax tissues during the adult phase. The complex nature of its cuticle allows for the clear recording of air pollutant deposits, providing data that is more representative than fluctuating physical air measurements. This species is known for its resilience, long-term exposure to high atmospheric pollutants can affect its wing morphology and flight patterns. O. sabina is not merely an inhabitant of the ecosystem but a reliable "natural sensor" for assessing air health quality. The utilization of this species as a biomonitoring model is expected to facilitate the mapping of air pollution zones in urban areas more efficiently and economically.